2008
DOI: 10.1063/1.2942391
|View full text |Cite
|
Sign up to set email alerts
|

Improved a-plane GaN quality grown with flow modulation epitaxy and epitaxial lateral overgrowth on r-plane sapphire substrate

Abstract: The authors demonstrate superior crystal quality of a-plane GaN grown on r-plane sapphire substrate based on the flow modulation epitaxy (FME) technique, in which the Ga atom supply is alternatively switched on and off with continuous nitrogen supply. With the FME technique, a high growth rate of 2.3μm∕h can still be achieved. With or without epitaxial lateral overgrowth (ELOG), either c- or m-mosaic condition is significantly improved in the samples of using FME. With ELOG, the surface roughness can be reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The same flow modulation scheme was applied to grow a-plane GaN films on r-plane sapphire substrate and the surface roughness of the sample was found to be less than half of conventionally grown sample [7]. On the other hand, NH 3 flow rate modulation with a constant Ga supply in MOCVD was found to improve lateral growth rate [8].…”
Section: Introductionmentioning
confidence: 96%
“…The same flow modulation scheme was applied to grow a-plane GaN films on r-plane sapphire substrate and the surface roughness of the sample was found to be less than half of conventionally grown sample [7]. On the other hand, NH 3 flow rate modulation with a constant Ga supply in MOCVD was found to improve lateral growth rate [8].…”
Section: Introductionmentioning
confidence: 96%
“…The problem can be avoided by growing GaN in nonpolar orientations, in which the polar c-axis is at 901 to the growth direction; alternatively, the electric field can also be reduced by growing in semipolar orientations, in which the c-axis is at an acute angle to the growth plane [2]. So recently there have been considerable interests in the growth of nonpolar and semipolar gallium nitride based on epitaxial films, heterostructures and devices [3][4][5][6][7][8]. The polar properties of GaN make the behaviors of the different polar directions distinct, especially when there is impurity incorporated.…”
Section: Introductionmentioning
confidence: 98%
“…We observed the minimum XRC FWHMs at 10 nm TiN interlayer, where the on-axis values were 432 arcsec and 497 arcsec along c-axis and m-axis, respectively. The results are much better than that with the traditional ELOG method, even the combination of ELOG and flow modulation epitaxial technique [7,15,16]. Before 10 nm TiN, the FWHM decreases with increasing TiN thickness, which indicates that the TiN interlayer has a significant effect on decreasing dislocation in the a-plane GaN.…”
Section: Resultsmentioning
confidence: 57%
“…It is evident from the TEM that both TDs and BSF densities decreased as a result of the TiN interlayer, which is consistent with our XRC findings. Previous work reported that the coalescence was incomplete until the overgrowth thickness achieving around 8 mm for the traditional ELOG method with a 20 mm wing region [16].…”
Section: Resultsmentioning
confidence: 99%